Activated leukocyte cell adhesion molecule soluble form: a potential biomarker of epithelial ovarian cancer is increased in type II tumors. Issue 11 (13th December 2012) - Carbotti, Grazia; Orengo, Anna Maria; Mezzanzanica, Delia; Bagnoli, Marina; Brizzolara, Antonella; Emionite, Laura; Puppo, Andrea; Centurioni, Maria Grazia; Bruzzone, Milena; Marroni, Paola; Rossello, Armando; Canevari, Silvana; et al.
Abstract Activated leukocyte cell adhesion molecule (ALCAM) is involved in cell–cell interactions in cancer. Shedding of its ectodomain by the metalloprotease ADAM17/TACE generates a soluble form (sALCAM). Here, we show that serum sALCAM levels were significantly higher in epithelial ovarian cancer (EOC) (p < 0.005) than in controls. The performance of sALCAM as classifier, tested by receiver operating characteristic curve, resulted in an area under the curve (AUC) of 0.8067. Serum sALCAM levels showed direct correlation with Carbohydrate Antigen‐125 (CA125/MUC16). Moreover, significantly higher levels were found in type II tumors, even in stage I/II, suggesting that elevated sALCAM is an early feature of aggressive EOC. In addition, sALCAM levels were higher in ascites than in sera, suggesting local processing of ALCAM in the peritoneal cavity. In immunodeficient mice, intraperitoneally implanted with a human EOC cell line, human sALCAM progressively increased in serum and was even higher in the ascites. The biochemical characterization of the sALCAM in EOC sera and ascites, showed two predominant forms of approximately 95 and 65 kDa but no EOC‐specific isoform. In addition, full‐length transmembrane ALCAM but no soluble form was detected in tumor‐derived exosomes found in ascites. Finally, in vitro invasion assays showed that inhibition of ADAM17/TACE activity decreased EOC invasive properties, while opposite effects were mediated by a sALCAM‐Fc chimera and by an antibody interfering with ALCAM/ALCAM interactions. Altogether these data suggest that sALCAM is a marker of EOC, which correlates with more aggressive type II tumors, and that ADAM17/TACE activity and sALCAM itself mediate enhanced invasiveness.